STUDI KESEUAIAN PARAMETER FISIKA-KIMIA PERAIRAN UNTUK PENGEMBANGAN AREA BUDIDAYA IKAN DENGAN MEDIA KERAMBA JARING APUNG DI DANAU IE SAYANG - Rahmayanti, Fitria; Najmi, Nurul; Islama, Dini; Muliyana, Agusriati (JURNAL AKUAKULTURA, 2021)
This research was conducted to analyze the water physical and chemical parameters of Ie Sayang Lake for fish culture development area using floating net cages. The observations of water physical and chemical parameters were finds out from April to June 2021 at four stations. The recorded data of water physic-chemical parameters included temperature, current velocity, dissolved oxygen, water depth, pH and turbidity. The data obtained then scored by matching the data values with the criteria for the suitability of waters for fish culture in floating net cage. The results showed that the condition of the water physical and chemical parameters in Lake Ie Sayang is not suitable to be developed as a fish culture area using floating net cage. The water parameter values during research namely temperatur (30,1oC to 31,9oC), current velocity (15 to 19,5 cm/s), dissolved oxygen (2,86 to 5,25 mg/l), water depth (1,08 to 1,93 m), pH (6,13 to 6,35) and water tubidity (0,47 to 0,58 m).